STUDI DESKRIPTIF PERAN GURU DALAM MENANGANI ANAK SPEECH DELAY DI TK DARUSSALAM SUMENEP - Fardiansah, Dita; Abidin, Ratno; Gusmaniarti; Wahono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines the causes, consequences, and approaches to addressing speech delays in children. Some steps teachers can take include identifying children with these delays, adjusting teaching techniques and materials, providing positive responses, encouraging children's involvement in classroom activities, and collaborating with relevant parties. The primary focus is the role of teachers in managing children with speech delays, a condition in which children are unable to speak according to their developmental stage. This study aims to uncover how teachers manage early childhood children with speech delays at Darussalam Kindergarten in Sumenep. The method used is descriptive qualitative, involving explanations of the researcher's activities during observations, interviews, and observations. Data collection techniques include observations and interviews using pre-prepared questions. After data is obtained through observations and interviews, descriptions and analyses of the findings are conducted. The results of the study show that the role of teachers in overcoming speech barriers includes: communicating clearly while using hand gestures and proper articulation, repeating words simply while paying attention to the grammar of the spoken language, training children to speak correctly repeatedly and slowly, always considering the vocabulary used by children, controlling children to speak in all situations, and correcting children's incorrect speech with the help of parents or close family.